The Effectiveness of Positivism Group Psychotherapy Based on Frisch’s Theory in Promoting Happiness and Life Satisfaction of Breast Cancer Patients - Saeidi, Zahra; Asgharnejad, Ali Asghar (American Scientific Research Journal for Engineering, Technology, and Sciences, 2018)
The main objective was to investigate the effectiveness of positivism group psychotherapy based on Frisch’s Theory in promoting happiness and life satisfaction of breast cancer patients referring to counseling centers in Iran. We conducted a quasi- experimental design of pre- and post-test in which experimental and control groups were utilized. The statistical populations were people referring to three counselling centers in Iran in 2016. The experimental group received the psychotherapy intervention based on Frisch’s approach. At the end, both groups took the post-test. The quality of life questionnaire OL-BC, the Oxford Happiness Inventory, and the Satisfaction with Life Scale were used as the measurement tools. Data were analyzed using analysis of covariance (ANCOVA) procedure by SPSS. Results showed that there is a significant difference between the mean scores of the experimental and the control groups in post-test. This means that the positivism group psychotherapy based on Frisch’s theory was effective in promoting happiness and life satisfaction of breast cancer patients (P< 0.01). Furthermore, the results showed that the positivism group psychotherapy based on Frisch’s theory increased post-test scores of the experimental group in variables of life satisfaction and happiness (P <0.05). Results confirmed that the positivism group psychotherapy based on Frisch’s theory can be used as an effective intervention to promote life satisfaction and happiness of breast cancer patients.